Hama-Region, Syrien: Survey im Gebiet des mittleren Orontes - Bartl, Katrin (e-Forschungsberichte des DAI, 2023)
Due to its favorable conditions the area of the middle Orontes around the provincial capital Hama is one of the main settlement areas in western Syria. Archaeological surface prospecting carried out between 2003 and 2005 demonstrates the continuous use of this landscape since the Paleolithic period. In addition to numerous single period sites from the prehistoric periods, the settlement pattern comprises a number of large tall settlements, mostly located near the river valley of the Orontes and its tributary Sarut. Archaeological evidence indicates a high settlement density in the early and middle Bronze Age as well as the Roman/early Byzantine periods.